Perspektif Kasih Sayang Ibnu Rūmi dalam Kasidah Waṣala al-Habīb (Kajian Semiotika Riffaterre) - Moh. Ainur Ridha (Institut Agama Islam Negeri Metro, 2022)
Ibnu Rūmi is one of famous poet from Abbasiyah Chalipate. This Kasidah is composed by 10 verses of poet. That theme was gazal and the scheme was bahr mujstaṡ. This research intend to uncover the mean of this kasidah.The researcher used the descriptive-analyctical method, the metods to find and uncover problem in sistematicly and describe the substantion and also used the Riffaterre analytics. In Riffaterre analytics there are 4 process: unsustainable expression, heuristic and hermeneutic readings, matrix, model, variant and hipogram. Based on the research, kasidah of Waṣala al-Habīb by Ibnu Rūmi, there is multiple variants that represent with model ‘إلى هواها ارعويت’. This model reffering to “fidality” matrix that explained the sacrifice and love of Ibn Rumi to his love. Keywords: Riffaterre Semiotics, Kasidah, Waṣala al-Habīb, Ibnu Rūmi, and Fidality.